Коронавірусна хвороба у вагітних: сучасний стан питання - Рябоконь, Олена Вячеславівна; Черкаський, В. В.; Рябоконь, Юрій Юрійович; Riabokon, O. V.; Cherkaskiy, V. V.; Riabokon, Yu. Yu. (My University, 2021)
На підставі огляду наукової літератури висвітлено дані про перебіг COVID-19 у вагітних, перинатальну передачу вірусу та особливості лікування. На сьогодні встановлені певні особливості клінічних і лабораторних проявів COVID-19 у вагітних, які слід враховувати при ранній діагностиці захворювання та оцінці ступеня тяжкості хвороби. На особливу увагу заслуговують хворі вагітні у II-III триместрах, оскільки є повідомлення про значне погіршення перебігу інфекції з швидким прогресуванням гострої дихальної недостатності та поліорганної недостатності в перинатальному або післяпологовому періоді. У лікуванні вагітних з тяжким і критичним перебігом коронавірусної хвороби на сьогодні слід користуватися діючими у відповідній країні уніфікованими рекомендаціями. Based on inspection of scientific literature we can see information about current coronavirus disease COVID-19 in pregnant women and influence this infection on the course of pregnancy. Besides, we found out information about perinatal transmission and treatment features. Today we install certain features of clinical and laboratory manifestations of infection SARSCoV- 2 in pregnant women, certainly, we must consider all this things for early diagnosis of the disease and severity assessment COVID-19. What’s more, all pregnant women which are on the second and the third trimester especially need of direct care, because we have information about significant deterioration in the course of infection with rapid progression of acute respiratory failure and multiple organ failure in perinatal or postpartum period. All things considered, we should follow to acting and unified recommendations in own country, when we treat pregnant women with severe or critical current coronavirus disease COVID-19.
Coronavirus disease covid-19 in pregnant women: relevance of the issue
Keywords: COVID-19; вагітність; coronavirus disease COVID-19; the pregnant